2016
DOI: 10.1111/asj.12735
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the presence of grazing‐experienced heifers on the development of foraging behavior at the feeding station scale for first‐grazing season calves

Abstract: In this study, effects of grazing-experienced heifer presence on foraging behavior development at the feeding station (FS) scale for first-grazing season calves were determined. A group of four calves grazing alone (C), and another comprising four calves (Wc) and three grazing-experienced heifers (Wh), were alternately stocked every day for 2 h on the same pasture for 26 days. The foraging time budget for Wc was significantly longer than that for C (P < 0.05) on day 7, and was similar to that for Wh on all day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…This is consistent with findings of Lopes et al (24), who observed that heifers that had once experienced pasture instantly remembered how to graze the following year. The Mand S-calves took slightly longer to start to graze, probably because they had no social model or experienced individuals to emulate (33,34). Also, inexperienced heifers spend more time exploring and tasting grass than ingesting it, compared to experienced heifers (33), which was numerically the case for our M-and S-calves here before they started grazing, even though exploring time was not long enough to statistically analyze it (data not shown).…”
Section: Effect Of Early Dam-calf Contact and Grazing Experience On Cmentioning
confidence: 77%
See 1 more Smart Citation
“…This is consistent with findings of Lopes et al (24), who observed that heifers that had once experienced pasture instantly remembered how to graze the following year. The Mand S-calves took slightly longer to start to graze, probably because they had no social model or experienced individuals to emulate (33,34). Also, inexperienced heifers spend more time exploring and tasting grass than ingesting it, compared to experienced heifers (33), which was numerically the case for our M-and S-calves here before they started grazing, even though exploring time was not long enough to statistically analyze it (data not shown).…”
Section: Effect Of Early Dam-calf Contact and Grazing Experience On Cmentioning
confidence: 77%
“…This is consistent with the selection of vegetation by stratum by experienced grazing cows under rotational grazing (35): once the upper layer is grazed, the height of the patch decreases, moving down to the lower layers (26). However, the botanical selection of the vegetation seemed different between groups: M-and S-calves ingested mainly grasses during the first days, as grasses are almost exclusive in the top layer, and then increasingly legumes and forbs [present in the intermediate and low layers, because of their smaller size; (34)]. On the contrary, D-calves constantly selected grasses until the seventh day of observation, whatever the height of the layer present on the plot.…”
Section: Effect Of Early Dam-calf Contact and Grazing Experience On Cmentioning
confidence: 99%
“…Other studies have observed that social facilitation of grazing behaviour leads the calf to develop suitable grazing techniques within days of birth (Kerr and Wood-Gush 1987b;von Keyserlingk and Weary 2007;Arrazola et al 2020). Foraging with experienced grazing partners up to 10 months older than experimental animals has also been shown to increase the consumption of novel feeds, increase grazing intensity, and reduce the latency to commence grazing in the hours to days after mixing (Velázquez-Martínez et al 2010;De Paula Vieira et al 2012;Shingu et al 2017). Costa et al (2016) and Hessle (2009) found that the effects of an experienced grazing companion were highest in the first 1-3 days postmixing.…”
Section: Animal Production Sciencementioning
confidence: 99%
“…Vitale et al (1986), for instance, observed semi-wild calves from birth to 2 months, recording peaks of play and grazing activity almost simultaneously in the early to mid-morning and late afternoon, with long bouts of lying and inactivity during the middle of the day. Many of these behaviours, such as grazing and lying, are believed to be socially facilitated, and may be modelled to calves by older, more experienced members of the herd (Shingu et al 2017;Mattiello et al 2019; see review by Whalin et al (2021)).…”
Section: Introductionmentioning
confidence: 99%